An overlooked sibling of the fruit-piercing moth Eudocima phalonia (Linnaeus, 1763) from Africa (Lepidoptera, Erebidae, Calpinae) - Brou Jr., V. A.; Zilli, A. (Zootaxa, 2016)
In recent years, we have been investigating the tropical calpine genus Eudocima Billberg, 1920 (Lepidoptera, Erebidae, Calpinae) with the intent of producing a generic revision. There are a number of undescribed species and here we describe as new a closely related species to the widespread and economically important fruit-piercer Eudocima phalonia (Linnaeus, 1763) (= fullonia Clerck, 1764), with which it has long been confused. Study material came from the private collection of Vernon Antoine Brou collection (VAB) and the Natural History Museum, London (NHM).